Basic Concepts of Structural Design for Architecture Students - Khodadadi, Anahita (Open textbook library., 2021)
This book aims to narrate fundamental concepts of structural design to architecture students such that they have minimum involvement with math problem-solving. Within this book, students learn about different types of loads, forces and vector addition, the concept of equilibrium, internal forces, geometrical and material properties of structural elements, and rules of thumb for estimating the proportion of some structural systems such as catenary cables and arches, trusses, and frame structures.